Induced Pluripotent Stem Cells: Challenges and Opportunities for Cancer Immunotherapy - Sachamitr, Patty; Hackett, Simon; Fairchild, Paul Jonathan (Frontiers in Immunology, 2014)
Despite recent advances in cancer treatment over the past 30 years, therapeutic options remain limited and do not always offer a cure for malignancy. Given that tumour associated antigens (TAA) are, by definition, self-proteins, the need to productively engage autoreactive T cells remains at the heart of strategies for cancer immunotherapy. These have traditionally focussed on the administration of autologous monocyte-derived dendritic cells (moDC) pulsed with TAA, or the ex vivo expansion and adoptive transfer of tumour infiltrating lymphocytes (TIL) as a source of TAA-specific cytotoxic T cells (CTL). Although such approaches have shown some efficacy, success has been limited by the poor capacity of moDC to cross-present exogenous TAA to the CD8+ T cell repertoire and the potential for exhaustion of CTL expanded ex vivo. Recent advances in induced pluripotency offer opportunities to generate patient-specific stem cell lines with the potential to differentiate in vitro into cell types whose properties may help address these issues. Here we review recent success in the differentiation of NK cells from human induced pluripotent stem (iPS) cells as well as minor subsets of DC with therapeutic potential, including CD141+XCR1+ DC, capable of cross-presenting TAA to naïve CD8+ T cells. Furthermore, we review recent progress in the use of TIL as the starting material for the derivation of iPSC lines, thereby capturing their antigen specificity in a self-renewing stem cell line, from which potentially unlimited numbers of naïve TAA-specific T cells may be differentiated, free of the risks of exhaustion.